DESKRIPSI KESALAHAN BELAJAR PESERTA DIDIK BERDASARKAN TAHAPAN KASTOLAN PADA MATERI BANGUN RUANG SISI DATAR DI KELAS VIII SMPN 11 PADANG - ADELLIA AYESHA (Departemen Matematika, 2022)
This study aims to describe (1) the learning errors shown in the mathematics learning process and (2) the learning errors shown in the mathematics learning outcomes of the eighth grade students of SMPN 11 Padang. The source of data in this research is using purposive sampling. Students are grouped into three categories of high, medium, and low learning achievement. Data collection using tests and interviews. The results of the study showed that the errors made by students in solving the problem of building a flat side space were Conceptual Errors and Procedural Errors. The cause of student errors in solving the problem of building a flat side space is influenced by several causes. The causes of conceptual errors include (1) Students do not understand the meaning of the problem, (2) Students are wrong in choosing the formula, and (3) Students cannot apply the formula properly. The causes of procedural errors include (1) Students do not follow the steps in solving problems, (2) Students lack practice in working on questions, and (3) Students are not able to solve problems to a simple stage. Keyword: Build a flat side space, Description, Student learning errors